KOMUNIKASI CITY BRANDING “BADUNG THE SOUL OF BALI” UNTUK MEMASARKAN DAYA TARIK WISATA OLEH DINAS PARIWISATA KABUPATEN BADUNG - Sagrario, Johanes; Dewi, LGLK.; Dewi, NGAS. (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2023)
One type of tourism marketing in an area is through city branding. Badung Regency has had a city branding with the slogan